2023
DOI: 10.3390/biology12091243
|View full text |Cite
|
Sign up to set email alerts
|

A549 as an In Vitro Model to Evaluate the Impact of Microplastics in the Air

Chman Shahzadi,
Alessandra Di Serafino,
Eleonora Aruffo
et al.

Abstract: Airborne microplastics raise significant concerns due to their potential health impacts. Having a small size, larger surface area, and penetrative ability into the biological system, makes them hazardous to health. This review article compiles various studies investigating the mechanism of action of polystyrene micro- and nanoplastics affecting lung epithelial cells A549. These inhalable microplastics damage the respiratory system, by triggering a proinflammatory environment, genotoxicity, oxidative stress, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…In our current research, we utilized A549 cells, a human lung adenocarcinoma cell line, and specifically employed PS-NPs as surrogates to explore the respiratory toxicity associated with airborne NPs. The selection of PS-NPs 800 nm was deliberate since this particular size range has been poorly investigated (27), and prior studies have linked distinct toxicities with different particle sizes (21,44). Moreover, it is well known that developing analytical methodologies to identify and quantify plastic particles in complex matrices is an urgent need for research concerning quantitative toxicity assessment of plastic pollution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our current research, we utilized A549 cells, a human lung adenocarcinoma cell line, and specifically employed PS-NPs as surrogates to explore the respiratory toxicity associated with airborne NPs. The selection of PS-NPs 800 nm was deliberate since this particular size range has been poorly investigated (27), and prior studies have linked distinct toxicities with different particle sizes (21,44). Moreover, it is well known that developing analytical methodologies to identify and quantify plastic particles in complex matrices is an urgent need for research concerning quantitative toxicity assessment of plastic pollution.…”
Section: Discussionmentioning
confidence: 99%
“…The internalization of PS particles is a crucial step for cellular toxicity, and several processes involved in the mechanism of internalization have been proposed, depending upon the physiology of particles, such as size, charge, zeta potential, and shape (27). In this study, the internalization of PS-NPs (800 nm) was first suggested by alteration of the internal complexity or granularity (i.e., side scatter) of cells in a concentration-dependent manner (Supplementary Figure S7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation